Anti-obesity effects of corn peptide on 3T3-L1 preadipocytes and C57BL/6J obese mice. Issue 3 (2nd November 2022) - Zhang, Shanshan; Kong, Lingzhe; Jia, Ziqiu; Shao, Shuli; Pan, Lin; Wang, Weiyu; Sun, Yingning
ABSTRACT: Corn peptide (CP) is a small, natural, biologically active peptide obtained by protease-catalysed hydrolysis of corn. CP exerts antihypertensive, hypoglycaemic, antihyperlipidemic, antioxidant, and antitumor effects, as well as prevents cardiovascular and cerebrovascular diseases. Although CP plays a role in preventing obesity-related diseases, its role in reducing obesity has not yet been determined. In this study, we analysed the inhibitory effects of CP on lipid droplet accumulation in 3T3-L1 preadipocytes and high-fat diet (HFD)-induced C57BL/6J Obese Mice. The results show that CP could inhibit preadipocyte differentiation and oil accumulation in 3T3-L1 preadipocytes. Oral CP administration reduced serum triglyceride (TG) content, epididymal fat weight, abnormal liver fat droplet accumulation, and C/EBPα expression. Furthermore, combination of CP administration and exercise reduced body, liver, and adipose tissue weights; decreased serum total cholesterol (TC), triglyceride and low-density lipoprotein (LDL) levels; and inhibited hepatic lipid droplet accumulations and epididymal fat cell hypertrophy. Additionally, this combination inhibited the expression of transcription factors, C/EBPα, C/EBPβ, and PPARγ, and adipogenic factors, FABP4 in mice. In conclusion, oral administration of CP inhibited lipid droplet accumulation and counteracted HFD-induced obesity in mice.